2016
DOI: 10.3168/jds.2015-10529
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral calcium supplementation on productive and reproductive performance in Holstein cows

Abstract: The objectives of this experiment were to determine the effects of oral Ca supplementation on milk yield, body condition, pregnancy per artificial insemination (P/AI), and days to pregnancy in Holstein cows considered to be of low (LRM; no calving assistance, live singleton without retained placenta) or high (HRM; at least one of the following: dystocia, twins, stillbirth, retained placenta, or vulvo-vaginal laceration) risk of developing metritis. The hypotheses were that oral Ca supplementation during the ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
65
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 23 publications
3
65
2
1
Order By: Relevance
“…German farmers favored oral calcium supplementation as a preventive strategy (Table 2). Sound evidence is available about the efficacy of oral calcium supplementation to prevent hypocalcemia (Sampson et al, 2009;Oetzel and Miller, 2012;Blanc et al, 2014;Martinez et al, 2016). Furthermore, economic advantages have been demonstrated (McArt and Oetzel, 2015).…”
Section: Study Resultsmentioning
confidence: 99%
“…German farmers favored oral calcium supplementation as a preventive strategy (Table 2). Sound evidence is available about the efficacy of oral calcium supplementation to prevent hypocalcemia (Sampson et al, 2009;Oetzel and Miller, 2012;Blanc et al, 2014;Martinez et al, 2016). Furthermore, economic advantages have been demonstrated (McArt and Oetzel, 2015).…”
Section: Study Resultsmentioning
confidence: 99%
“…In another study, hypocalcemic cows were matched with normocalcemic cows based on parity and occurrence of health disorders, which would control for detrimental effects of increased diseased susceptibility in cows with SCH, and milk production was higher in hypocalcemic cows in early lactation (Jawor et al, 2012). Further, Oetzel and Miller (2012) and Martinez et al (2016b) found that cows with a higher herd rank in previous lactation milk production benefited from oral Ca bolus supplementation shortly after parturition and responded with higher early lactation milk yield. This suggests that higher-producing cows may be more susceptible to hypocalcemia, potentially due to a greater Ca drain for colostrum and milk production.…”
mentioning
confidence: 94%
“…On the other hand, numerous studies evaluating postpartum, serial serum calcium levels in cows not receiving supplemental calcium either remain constant or significantly decrease relative to baseline levels at calving. 8,13,15,20,22 Given the lack of a concurrent negative control, no definitive conclusions can be made.…”
Section: Resultsmentioning
confidence: 99%
“…11 Further, treatment with a calcium-containing bolus post calving was associated with a lower incidence of subclinical hypocalcemia, improved pregnancies per breeding, shorter days to pregnancy, and higher milk production in multiparous cows. [12][13][14] Other researchers have found equivocal effects of oral calcium supplementation on serum calcium, health, and reproductive outcomes. 15 There has been a very strong adoption of the oral calcium supplement by dairy producers throughout North America; however, many of the alternative products to this product have not been tested to demonstrate similar efficacy in influencing blood calcium levels.…”
Section: Introductionmentioning
confidence: 99%